2008
DOI: 10.2320/matertrans.mer2007252
|View full text |Cite
|
Sign up to set email alerts
|

Electromagnetic Interference Shielding Characteristics of Sn-Al Powder Coating Layers

Abstract: Sn-xAl powder complex materials are used as coating in building materials. This study coats complex colloid mixed with Sn-xAl powders and polyethylene on glass to examine the shield effect on electromagnetic interference (EMI). The results show that adding Al to the Sn-xAl powders can increase the electromagnetic interference (EMI) shield at lower frequencies. Notably, the number of cavities in the coating layer increased with the coating thickness, with the result that the EMI shield could not improve with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…The experiment was conducted by measuring the wavelength corresponding to perpendicular projection, while the frequency range was controlled in between 50MHz and 3000MHz. Meanwhile, the results of each measurement were averaged 3 to 7 points, and the effective shielding rate was observed by performing further calculations [10][11].…”
Section: Experimental Designmentioning
confidence: 99%
“…The experiment was conducted by measuring the wavelength corresponding to perpendicular projection, while the frequency range was controlled in between 50MHz and 3000MHz. Meanwhile, the results of each measurement were averaged 3 to 7 points, and the effective shielding rate was observed by performing further calculations [10][11].…”
Section: Experimental Designmentioning
confidence: 99%
“…Therefore, many studies have been conducted on the suitability of materials for shielding electromagnetic radiation [12][13][14][15]. With the aim of enhancing the shielding effect, Hung [16,17] used sputtered Sn-Al and Sn-Cu thin films and studied the crystallization mechanism, the impact of film thickness on electromagnetic interference (EMI) properties, and the shielding effect against EMI by coating a composite colloid containing a mixture of Sn-Al powder and polyethylene on glass. The study confirmed that the relationship between coating thickness and shielding was constrained by certain factors.…”
Section: Introductionmentioning
confidence: 99%
“…Up to now, many research teams have been actively exploring various shielding methods. In all the shielding methods, the surface treatment methods, such as conductive film [18,19] and conductive powder [20][21][22][23][24], have had better shielding effects. However, they are easy to wear, peel, oxidize, difficult to process and expensive, etc.…”
Section: Introductionmentioning
confidence: 99%